Effect of Bacterial Metabolites From Good Oral-Hygiene to Biofilm Formation From Poor Oral-Hygiene - Refyan, Sarah Athiyyahmaulidya; Ratna Ramadhani; Bachtiar, Endang Winiati; Bachtiar, Boy Muchlis; Sulistiadi, Wahyu (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Microbial variations and oral hygiene (OH) status of an individual are related to the oral biofilm formation. The metabolite of microorganisms influences biofilm formation. This research aims to analyse the effect of bacterial isolates' metabolites from a good OH individual on the in vitro biofilm of bacterial isolates from a poor OH individual. Materials and Methods: Spent medium of bacteria isolated from a good OH individual tongue swab that contains different protein and nitrate concentrations was treated in vitro with biofilm from a poor OH individual tongue swab to evaluate the cell viability and in vitro biofilm mass under aerobic conditions. The methods used include the Bradford test, Griess test, Crystal Violet test, and Total Plate Count. Results and Discussions: There were significant differences in the cell viability of bacteria isolated from poor OH individual treated by spent medium isolated from good OH individual with different concentrations of protein and nitrate (p value <0.05), as well as biofilm mass of the sample that was treated with spent medium containing different nitrate concentration (p value < 0.05). Conclusion: The protein and nitrate content in the spent medium from a good OH tongue swab can influence cell viability and in vitro biofilm mass from a poor OH individual tongue swab.